Multidisciplinary Systems Engineering Architecting the Design Process - Crowder, James A.; Carbone, John N.; Demijohn, Russell (Springer International Publishing : Imprint: Springer, 2016)
This book presents Systems Engineering from a modern, multidisciplinary engineering approach, providing the understanding that all aspects of systems design, systems, software, test, security, maintenance and the full life-cycle must be factored in to any large-scale system design; up front, not factored in later. It lays out a step-by-step approach to systems-of-systems architectural design, describing in detail the documentation flow throughout the systems engineering design process. It provides a straightforward look and the entire systems engineering process, providing realistic case studies, examples, and design problems that will enable students to gain a firm grasp on the fundamentals of modern systems engineering.  Included is a comprehensive design problem that weaves throughout the entire text book, concluding with a complete top-level systems architecture for a real-world design problem.